Opportunities For Using Interdisciplinary Relationships In Teaching Mathematics In Technical Higher Educational Institutions - Akhlimirzayev A.; Sodiqova GA (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
This in the article technique supreme training in their homeland teachable supreme mathematics of the course interdisciplinary relevance in providing wide to opportunities has that enough theoretical and practical issues using illuminating given.